(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Respiratory burst function resulting in the release of reactive oxygen species from leucocytes is one of the key mechanisms of innate immune system to prevent the establishment of intracellular pathogens in the host cells. Previous studies on COVID-19 patients concentrated on adaptive immunity while study on respiratory burst functions is lacking. Respiratory burst mediators levels [nitric oxide (NO) and hydrogen peroxide (H2O2)] and respiratory burst enzymes activities [Catalase (CAT), Myeloperoxidase (MPO) and Superoxide dismutase (SOD)] were quantitated in the plasma Mean plasma NO level, MPO activity and H2O2 level were significantly decreased while SOD activity was significantly increased in COVID-19 patients at admission compared with control. Mean plasma NO level significantly decreased while MPO activity was significantly increased in COVID-19 patients at discharge compared with control. Plasma NO level, H2O2 level and MPO activity were significantly increased in COVID-19 patients at discharge compared with COVID-19 patients at admission. In COVID-19 patients that spent ≥10days in admission, the levels of NO and H2O2 were significantly increased compared with the levels of NO and H2O2 in COVID-19 patients that spent <10days in admission. In male COVID-19 patients, NO level and MPO activity were significantly increased compared with MPO activity in female patients. In COVID-19 patients ≥40years of age, NO level was significantly decreased while MPO activity was significantly increased compared with COVID-19 patients <40yrs of age. In male COVID-19 patients, NO level and MPO activity was significantly increased compared with MPO activity in female patients. It could be concluded from this study that factors of respiratory burst which are components of the innate immune system are altered in COVID-19 patients and could be involved in the immune-pathogenecity of SARS-CoV-2; and that MPO coupled with NO may explain differential severities of COVID-19 among genders and age groups.